(untitled) (Jurnal Adabiya, 2022)
Abstract: Tracing the history of Aceh through traces of civilization that was built from the period of the Kingdom of Aceh Darussalam has been recorded in historical records as well as documentation in the form of pictures and map images. It is necessary to trace existing buildings and other objects from past human cultural works to explain the existence of civilization created from the two periodization of Aceh history. The method used is descriptive analysis. The results of the study describe that the objects produced during the Kingdom of Aceh Darussalam experienced development. During the Kingdom of Aceh Darussalam, crowds were more directed at the coast so that development in the interior was not so visible, while during the Dutch colonial period construction was carried out in almost all of Aceh, especially in the construction of land roads. It caused by the needs of the government related to the transportation of natural resources in the form of agricultural products produced by the community. In addition, road construction was also carried out to speed up the arrival of news from remote areas to cities and from the city center to the Dutch government in Singapore. The news delivery system is carried out through the post office and telegram. This study suggests the need for in-depth research related to archaeological traces by conducting excavations so that building structures can be found in order to reconstruct history through their remains.